Pengaruh Pendekatan Matematika Realistik Terhadap Pemahaman Konsep Siswa Kelas VIII Mtsn 1 Probolinggo - Nur Fadilah; Leny Nurkholisah M (CV Edujavare Publishing, 2025)
The understanding of mathematical concepts is still low among students at both the basic and secondary levels. The use of learning approaches should be a primary focus to achieve a good understanding of concepts. The Realistic Mathematic Education model can be used as a solution in mathematics education. This study aims to determine the effect of the Realistic Mathematics Educatio model on students conceptual understanding. The Realistic Mathematics Educatio model emphasizes the connection between mathematical concepts and real-life contexts, thus it is expected to enhance students understanding in a more meaningful way. This research is a quasi-experimental study with a Posttest-Only Group Control Design. The population of this study includes eighth-grade students of MTsN 1 Probolinggo. Data collection was carried out using a test instrumen in the form of an essay. The obtained data were analiyzed using descriptive statistics and inferensial tests-t. The sampling was conducted randomly after going throgh a class equivalence test. Data collection was conducted using a test instrumen in the form of description. The results of the data analysis show that conceptual understanding of students who learn using the Realistic Mathematics Educatio model is better than that of students who learn with the conventional approach. This indicates taht te implementation of the Realistic Mathematics Educatio model has an effect on students conceptual understanding.